Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1039/c2dt12114j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and bioimaging of a fluorescent rhenium-containing PNA bioconjugate

Abstract: A new rhenium tricarbonyl complex of a bis(quinoline)-derived ligand (2-azido-N,N-bis((quinolin-2-yl)methyl)ethanamine, L-N(3)), namely [Re(CO)(3)(L-N(3))]Br was synthesized and characterized indepth, including by X-ray crystallography. [Re(CO)(3)(L-N(3))]Br exhibits a strong UV absorbance in the range 300-400 nm with a maximum at 322 nm, and upon photoexcitation, shows two distinct emission bands at about 430 and 560 nm in various solvents (water, ethylene glycol). [Re(CO)(3)(L-N(3))]Br could be conjugated, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 47 publications
1
70
1
1
Order By: Relevance
“…Indeed, while the concentration of Re-myr-Tat in the cell medium was five times lower than that of the complex, the cells incubated with Re-myr-Tat appeared much brighter, indicating significantly higher uptake (it is important to keep in mind that the intensity of the emission signal of a compound in the cells sometimes fails to correlate with uptake, as luminescence can be quenched in the cellular environment). 28,64 In terms of subcellular localization, the complex and the bioconjugate were visualized in the cytoplasm (although weak signals were sometimes detected in the nucleoli of cells incubated with the complex), a localization typically observed for this type of Re complex.…”
Section: (Bipy)(py-alkyne)]mentioning
confidence: 99%
“…Indeed, while the concentration of Re-myr-Tat in the cell medium was five times lower than that of the complex, the cells incubated with Re-myr-Tat appeared much brighter, indicating significantly higher uptake (it is important to keep in mind that the intensity of the emission signal of a compound in the cells sometimes fails to correlate with uptake, as luminescence can be quenched in the cellular environment). 28,64 In terms of subcellular localization, the complex and the bioconjugate were visualized in the cytoplasm (although weak signals were sometimes detected in the nucleoli of cells incubated with the complex), a localization typically observed for this type of Re complex.…”
Section: (Bipy)(py-alkyne)]mentioning
confidence: 99%
“…[53] However, our group and others have previously reported that, in some cases, luminescence microscopy can provide inconclusive results on the cellular localization of metal complexes, because of their low emission quantum yields or luminescence quenching. [20,22,68,69] Therefore, we decided to investigate the cellular uptake and organelles localization of the two complexes via ICP-MS. [70] The cellular uptake of 1 and 2 was evaluated on HeLa cells to compare these results with the luminescence microscopy images. HeLa cells were incubated with 1 (4 and 20 μM) and 2 (4 μM) for 4 h in the dark, and the metal content in the entire cell and in the different cellular fractions was then detected by using ICP-MS analysis; the results are reported in Figure S15.…”
Section: Intracellular Localization and Quantificationmentioning
confidence: 99%
“…35 Recently, this approach was extended to allow functionalization with different and multiple organometallic moieties 7, potentially giving the resulting oligomer a variety of electrochemical and spectroscopic properties. 31,36 The main application of ferrocene-functionalized oligonucleotides is electrochemical sensing, with a common approach being immobilization on gold electrodes using terminal thiol groups. 15,17,18,37 Such systems typically monitor the changes in current (arising from oxidation of the tag) between singlestranded and duplex DNA, with the unbound probe strand sometimes formed into a hairpin (Figure 3).…”
mentioning
confidence: 99%
“…Ferrocene, 28,29 cobaltocenium 6, 29 rhenium and technetium tricarbonyls, 30,31 and ruthenocene 32 have all been tagged to PNA using amide bond forming reactions. Click chemistry has also been used, both to introduce ferrocene to the center of the strand 33 and to synthesize a family of ferrocene-conjugated PNA probes, 34 with the thermal stability of duplexes formed with DNA then investigated.…”
mentioning
confidence: 99%